Length effect of metal-tip monopole antenna to temperature distributions for microwave ablation - Chaichanyut, M.; Lertprasert, P.; Phonphruksa, P.; Tungjitkusolmun, S. (My University, 2007)
This paper present three-dimensional finite element analyses of hepatic cancer. We studied the characteristics of metal-tip monopole (MTM) antennas for microwave ablation by analyzing the length effect of metal at the antenna tip. We analyses microwave ablation at frequency of 2.45GHz.The length of metallic tip (ht) are varied so as to observe the effect on the temperature distribution. Simulations the length of metallic tip are 1mm, 2mm and 4 mm. From the simulation results, we considered the hepatic cancer region where temperature exceeds 50 °C. The lengths of metallic tip are 1 mm, 2 mm and 4mm had similar temperature distribution profiles and the maximum temperature occurred around the tips of the antennas. In case the length of metallic tip is 4mm, the temperature distribution was widest and induced the highest temperature in cancer tissue. In addition, the temperature distribution was narrowly shaped along the length in regions the shaft body of the antenna. For case the length of metallic tip is 2 mm, the temperature had minimum in cancer tissue and can be minimum ablation cancer tissue (17.34cm3). For case the length of metallic tip is 1 mm, this case can be maximum ablation cancer tissue (18.67cm3).
Keywords: Length effect; Microwave ablation; Temperature distribution